PENERAPAN MODEL PEMBELAJARANKOOPERATIF CRH (COURSE REVIEW HORAY) UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2011/2012 - Rosmaini S; Irda Sayuti; Rika Mulyani (Program Studi Pendidikan Biologi, 2012)
This research has been conducted to increase the scientific attitude and Biology learning outcomes with Cooperative CRH model in XI IPA1 SMAN 5 Pekanbaru at 2010/2011 school years. This research had been done on September-October 2011. The sampel amount to 39 students. The parameters were scientific attitude, Biology learning outcomes, students and teachers activities. Result showed, the average of scientific attitude on first cycle was 67,53% (sufficient), and the average of scientific attitude on second cycle 85,47% (good). The average absorption of students on first cycle was 58,69% (less), and daily test students was 75,43% (less), at second cycle the average absorption of students increased 78,92 (sufficient) and daily test 79,46% (sufficient). Learning outcomes students on first cycle was 51,28% (complete) and 48,72% (notcomplete). Learning outcomes students on second cycle was 82,05% (complete) and 17,95% (notcomplete). The group appreciation on first cycle for super was 4 groups and great 4 groups. All groups get the great appreciation on second cycle. Students activities on first cycle was 61.01% (cufficient) and on second cycle 85,50% (good). Teacher activities on first cycle was 88,45% (best), and on second cycle 4,23% (best). The conclusion was Cooperative CRH model could increased scientific attitude and Biology learning outcomes students of XI IPA1 SMAN 5 Pekanbaru at 2011/2012 school years.Keywords: Cooperative CRH Model, Biology learning outcomes, scientific attitude